2014
DOI: 10.1182/blood-2014-02-555953
|View full text |Cite
|
Sign up to set email alerts
|

Postartesunate delayed hemolysis is a predictable event related to the lifesaving effect of artemisinins

Abstract: Key Points After being killed by artesunate, malaria parasites are expelled from red cells and then these pitted red cells reenter the circulation. When many pitted red cells are produced during therapy, their delayed clearance a few weeks later triggers hemolytic episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
170
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(181 citation statements)
references
References 30 publications
9
170
1
1
Order By: Relevance
“…In the absence of malaria parasites, free iron bioactivation of the endoperoxide bridge of artemisinin drugs can be used to modulate its effects (Conran, 2014;Krishna et al, 2004;Meshnick et al, 1989;Meshnick et al, 1993;Muhia et al, 1994;Tangnitipong et al, 2012). Delayed hemolysis in AS group follows a pattern similar to that reported in malaria infected persons (Arguin, 2014;Boillat et al, 2015;Chavada et al, 2015;Conran, 2014;Jauréguiberry et al, 2014;Kurth et al, 2016;Lee et al, 2015;Rehman et al, 2014;Rolling et al, 2015;WHO, 2013), although no anemia was recorded throughout this study.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In the absence of malaria parasites, free iron bioactivation of the endoperoxide bridge of artemisinin drugs can be used to modulate its effects (Conran, 2014;Krishna et al, 2004;Meshnick et al, 1989;Meshnick et al, 1993;Muhia et al, 1994;Tangnitipong et al, 2012). Delayed hemolysis in AS group follows a pattern similar to that reported in malaria infected persons (Arguin, 2014;Boillat et al, 2015;Chavada et al, 2015;Conran, 2014;Jauréguiberry et al, 2014;Kurth et al, 2016;Lee et al, 2015;Rehman et al, 2014;Rolling et al, 2015;WHO, 2013), although no anemia was recorded throughout this study.…”
Section: Discussionsupporting
confidence: 59%
“…Different hypothesis have been proposed to explain the underlying cause of hemolysis after artemisinin treatment, however the hypothesis that pitted erythrocytes are destroyed during recovery best explains post-artesunate delayed hemolysis after treatment of malaria infection (Jauréguiberry et al, 2014). Hemolysis may occur after treatment with different classes of antimalarials ISSN: 2198-4093 www.bmrat.org (Ngole et al, 2010;Price et al, 2001;Sowunmi et al, 2009), however studies have not reported delayed post-treatment hemolysis occurring with antimalarials other than artemisinin derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Early destruction of pitted erythrocytes has been the leading hypothesis for postartesunate delayed hemolysis since it was first recognized a few years ago.…”
mentioning
confidence: 99%
“…The delayed, synchronous destruction of this population of pitted erythrocytes accounts for the delayed hemolysis. 20 Hemolysis with exposure of RBCs to high doses of several artemisinin derivatives has also been described in vitro. 21 …”
Section: Discussionmentioning
confidence: 99%